Unravelling Older Adults’ Continuance Intention on Social Networking Sites Through the Lens of SOR Theory: Older Adults’ Continuance Intention on Social Networking Sites - Chew, Tze Ha; Chin, Christie Pei-Yee; Sondoh Jr., Stephen L. (Journal of Technology Management and Business, 2024)
The rise of social networking sites (SNS) has transformed the digital landscape, especially for older adults. While previous studies have explored various theoretical frameworks like the Technology Acceptance Model (TAM) and Social Support Theory (SST), there’s a need for a deeper understanding of older adults’ motivations and behaviors on these platforms. This study addresses this gap by applying the Stimulus–Organism–Response (SOR) theory to examine how older adults’ perceptions influence their continued use of SNS. This framework considers various factors such as platform quality (PQ), content quality (CQ), knowledge self-efficacy (SE), and social connectedness (SC). It also incorporates perceived enjoyment (PE), self-disclosure (SD), and subjective well-being (WB) as internal states, with SNS continuous use intention (SU) as the ultimate response. Additionally, the study includes habit (HB) as a mediator in the relationship between subjective well-being and SNS continuous use intention. Survey data from 190 older adults in Sabah, Malaysia, were collected for this study, and partial least squares structural equation modelling (PLS-SEM) was employed to validate the proposed framework. PQ, CQ, and SE significantly and positively affect WB and PE. SC positively impacts PE but is not significant with WB. WB mediates the relationships between PQ, CQ, SE, and SU. Additionally, HB mediates the effect of WB on SU. In conclusion, this study emphasises the transformative potential of technological solutions within SNS, offering practical implications for creators and providers. It contributes to developing effective strategies to enhance the SNS experiences of older adults.